A modified fluorescent probe protocol for evaluating the reactive oxygen species generation by metal and metal oxide nanoparticles in Gram-positive and Gram-negative organisms - Anmiya Peter; Jiya Jose; Sarita G. Bhat; Abhitha K (Results in Engineering, 2024)
Nanomaterials have enormous potential for application, particularly in the health sector. It is imperative to find new methods to develop new antibacterial drugs that suppress bacterial-resistant infections and restrict the spread of dangerous infectious diseases. Some metal and metal oxide nanomaterials can generate reactive oxygen species (ROS) in bacterial cells that can prevent bacterial infections. ROS plays a role in both healthy and pathological cellular processes. These extremely reactive compounds include hydrogen peroxide, superoxide, singlet oxygen, and hydroxyl radical. Several fluorescent probes are very selective and specific for certain ROS, particularly for their detection. Furthermore, it is crucial to comprehend the mechanism of ROS generated by nanomaterials because ROS are involved in several cellular signalling pathways. This work portrays a modified protocol for detecting ROS production in Gram-positive and Gram-negative organisms using fluorescent probes. Here, we use Dichloroflurosceine diacetate (DCFDA) to glimpse ROS production. This probe is specifically used for the detection of ROS in cell lines. We modified the protocol for analysing intracellular ROS production in bacteria in the presence of different metal and metal oxide nanomaterials and the detection of photocatalyzed ROS generation from nanoparticles. Scanning electron microscopy (SEM) images confirm the ROS-mediated bacterial cell rupture.